Tourism demand index and its correlation with standard of living in EU countries - Majchrzak-Jaszczyk, Anetta (Turystyka i Rozwój Regionalny, 2022)
Tourism is one of the fastest growing industries in the world. This study proposes construction of tourism demand index and direct application of this index to rank chosen countries. The second aim is to analyze if the place in ranking is correlated with citizens’ standard of living.Six measures of tourism demand for 27 EU countries were collected from Eurostat for the year 2019. As a standard of living measure, Human Development Index (HDI) was taken. As a result, high and positive correlation between almost all types of tourism demand indexes and HDI was noticed. The place of a particular country in the ranking depends on the kind of tourism demand measure, which was used. The method of constructing tourism demand index proposed in the article can be used for other group of countries or regions.